Pre- and post-emergent application effects of nemafric-bg phytonematicide on growth of potato cultivar 'mondial g3' and suppression of meloidogyne javanica - Huma, Tiego Isaac (My University, 2019)
Available potato (Solanum tuberosum L.) cultivars do not have any genotype that is resistant to the root-knot (Meloidogyne species) nematodes. Due to the susceptibility of potato cultivars to Meloidogyne species, alternative management strategies had to be researched and developed after the withdrawal of methyl bromide from the agro-chemical markets, amongst which were the cucurbitacin-containing phytonematicides. However, of the available application methods of phytonematicides, the ground leaching technology (GLT) and botinemagation technology were not suitable for use in most high-rainfall potato-producing regions, where production is under rain-fed conditions. The objective of the study, therefore, was to determine whether pre- and post-emergent application of Nemafric-BG phytonematicide would have effects on growth of potato and suppression of M. javanica population densities. Parallel pot trials of pre- and post-emergent application of Nemafric-BL phytonematicide were conducted under greenhouse conditions in autumn (February-April: Experiment 1) 2017 and validated (Experiment 2) in 2018. Each plant was inoculated with 3000 M. javanica eggs and second-stage juveniles (J2). Five treatments, namely, 0, 2, 4, 8 and 16 g concentration of Nemafric-BG phytonematicide, arranged in randomised complete block design, were either applied mixed with seed tubers for pre-emergent or spread on the soil surface after emergence for post-emergent trials. In all cases, plant growth variables were assessed using the Curve-fitting Allelochemical Response Data (CARD) model, whereas nutrient elements (Fe, K, Na and Zn) and nematode variables were assessed using analysis of variance, with data subjected to lines of the best fit. In pre-emergent application trial, plant height (R2 = 0.98) and fresh root mass (R2 = 0.99) exhibited quadratic relations, characterised by density dependent growth patterns with increasing concentrations of Nemafric-BG xv phytonematicide in Experiment 1, similar trends were also observed on plant height (R2 = 0.99) and root mass (R2 = 0.99) in Experiment 2. In contrast, in post-emergent application trial, plant height (R2 = 0.97), fresh root mass (R2 = 0.99) and dry shoot (R2 = 0.98) exhibited quadratic relations in Experiment 1, which ascribed to DDG patterns, similar trends were also observed in Experiment 2 on plant height (R2 = 0.99), fresh root mass (R2 = 0.96) and dry shoot (R2 = 0.99) of potato cv. ꞌMondial G3ꞌ. In pre-emergent application trials, Mean Concentration Stimulation Point (MCSP) = 24.18 and 7.82 g, respectively, in Experiment 1 and Experiment 2, with ∑k being equivalent to 20 and 6 units for potato to the product, respectively, in Experiment 1 and Experiment 2. In contrast, post-emergent application trials, MCSP = 9.87 and 12.10 g, respectively, in Experiment 1 and Experiment 2, whereas the ∑k value for potato to the product was 11 and 6 units, respectively in Experiment 1 and Experiment 2. Increasing concentrations of the phytonematicide significantly (P ≤ 0.05) affected the selected nutrient elements. In pre emergent application trials, K (R2  =  0.96) Na (R2  =  0.90) and Zn (R2  =  0.83) each with increasing Nemafric-BG phytonematicide concentrations exhibited positive quadratic fashion, while Fe (R2  =  0.87) exhibited negative quadratic relations in Experiment 1. In Experiment 2, K (R2  = 0.99), Na (R2  = 0.90) and Zn (R2 =  0.97) contents each in leaf tissues against the increasing concentrations of the phytonematicide exhibited negative quadratic relations, while Fe (R2  = 0.88) exhibited positive quadratic relations. In post emergent trials, Fe (R2 = 0.91, Na (R2 = 0.90) and Zn (R2 = 0.99) contents in leaf tissues against increasing Nemafric-BG phytonematicide concentration exhibited negative quadratic relations, whereas K (R2 = 0.86) exhibited positive quadratic relation in Experiment 1. In Experiment 2, Fe (R2 = 0.93), K (R2 = 0.92), Na ( R2  = 0.79) and Zn (R2 xvi = 0.89) contents in leaf tissues of potato exhibited positive quadratic, respectively. In pre emergent trial for Experiment 1, eggs in roots (R2 = 0.78), J2 in roots (R2 = 0.85), J2 in soil (R2 = 0.97) and Pf (R2 = 0.78) of M. javanica against increasing pre-emergent application concentrations of Nemafric-BG phytonematicide exhibited negative quadratic relations, characterised by DDG patterns. Similar trends were observed on eggs in roots (R2 = 0.82), J2 in roots (R2 = 0.99), J2 in soil (R2 = 0.84) and Pf (R2 = 0.85) in Experiment 2. In contrast, in post-emergent application trial, eggs in roots (R2 = 0.87), J2 in roots (R2 = 0.99), J2 in soil (R2 = 0.91) and Pf (R2 = 0.99) of M. javanica against increasing post emergent application concentrations of Nemafric-BG phytonematicide also exhibited negative quadratic relations in Experiment 1, which ascribed to DDG patterns. Similar trends were also observed on eggs in roots (R2 = 0.72), J2 in roots (R2 = 0.68), J2 in soil (R2 = 0.85) and Pf (R2 = 0.83) in Experiment 2. Results from the study demonstrated that Nemafric-BG phytonematicide stimulated plant growth at lower concentration and the product does not have any detrimental effects in accumulation of nutrient elements in leaf tissues. Therefore, it is concluded, that the product could be applied at the recommended rates of 7.82 and 9.87 g/plant in pre and post-emergent application, respectively, for the management of root-knot nematodes, provided the active ingredient does not accumulate in potato tubers or have any detrimental effects in accumulation of nutrient elements in tubers and temper with nutritional value of potatoes.
Thesis (M. A. Agriculture (Plant Protection)) -- University of Limpopo, 2019
Keywords: Meloidogyne species; Root-knot nematodes; Potato cultivars; Root-knot nematodes; Plant nematodes; Plant nematodes -- Biological control; Potatoes -- Breeding